2020
DOI: 10.1039/c9py01939a
|View full text |Cite
|
Sign up to set email alerts
|

Engineering digital polymer based on thiol–maleimide Michael coupling toward effective writing and reading

Abstract: Based on thiol–maleimide Michael coupling, a digital polymer allowing efficient message writing and reading was rationally designed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…To address this issue, the chemical structure of monomers can be optimized to decrease their MS/MS reactivity and hence lower the number of dissociation pathways per repeating unit. [ 13,14 ] Using this strategy, the longest chain read so far by MS/MS alone is a 77‐mer. [ 4 ] Increasing the number of encoded bits per monomer is another efficient strategy to enhance the storage capacity of a single chain.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, the chemical structure of monomers can be optimized to decrease their MS/MS reactivity and hence lower the number of dissociation pathways per repeating unit. [ 13,14 ] Using this strategy, the longest chain read so far by MS/MS alone is a 77‐mer. [ 4 ] Increasing the number of encoded bits per monomer is another efficient strategy to enhance the storage capacity of a single chain.…”
Section: Introductionmentioning
confidence: 99%
“…Such structural designs always aim at reducing the number of dissociation routes, in order to avoid signal dilution when dealing with long chains, while still enabling full sequence coverage. For this purpose, different strategies have been reported: removing reactive functions, [14] controlling the oxidation degree of specific atoms, [15] or introducing linkages of low dissociation energy to make any other bonds MS/MS silent [16] . The latter approach was successfully employed to decipher large amounts of information stored in sequence‐defined poly(phosphodiester)s using a routine mass spectrometer [17] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to capitalize on the robustness of the phosphoramidite used in the automated synthesis of long poly(phosphodiester)s, specific reagents were prepared to include alkoxyamine linkages in the final chains, the low bond dissociation energy of which makes all phosphate bonds MS/MS‐silent, lowering the number of product ion series from eight to two and hence ensuring full sequence coverage of long chains 15 . Similarly, Zhang and co‐workers recently showed that controlling the oxidation degree of sulfur atoms in the backbone of poly(succinimide thioester)s drastically enhances dissociation selectivity 16 . In addition to re‐engineering structures, fragmentation of synthetic polymers can also be manipulated by appropriate adjustments of experimental parameters in the ionization step.…”
Section: Introductionmentioning
confidence: 99%